STUDI KOMPARASI PERKEMBANGAN INDUSTRI BESAR DAN SEDANG (IBS) ANTARA KOTA SEMARANG DAN KABUPATEN CILACAP TAHUN 2001-2010 - , Heriani Sembiring, Ir. Kawik Sugiana, M.Eng.,Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Large and Medium Industries (LMI) has a very important role in the economic development of Central Java. Growth in the industrial sector will be able to provide jobs, provide for goods and services and contribute to the formation of Gross Domestic Product (GDP). Economic activity Semarang and Cilacap Districts contributed approximately 21.50% to the GDP formation of Central Java while spacious two regions are only 8.07%. The added value resulting from the industrial sector in both regions reached 20.33%. Both of these regions also have a means of supporting industrial facilities are very complete as airports and ports. This study aims to: (a) determine the different levels of development LMI in Semarang and Cilacap, and (b) identify the factors influencing the different levels of development. The variables used in this study include four factors, namely physical factors (raw materials, roads, airports, ports and electricity)